TANGGUNG JAWAB NOTARIS DALAM PEMBUATAN PERJANJIAN SUBROGASI DENGAN JAMINAN HAK ATAS TANAH DI KOTA BATAM - Agus Riyanto (Jurnal Cahaya Keadilan, 2017)
Banking has a strategic position as an intermediary institution andsupport payment system. To guarantee the loan or financing providedby the bank to the debtor or customer, the bank will charge thecollateral to the customer. In practice, credit already secured bycollateral is often carried out take-over. Take over is chosen by thecommunity because for various reasons, such as simple credit procedures and the time required is also relatively fast. This researchtries to analyze the responsibility of Notary in making takeoveragreement specially if loan / credit is secured with right of land. Themethod used in this research is normative. Where researchers get datafrom literature studies which will then be tested with legal principles.The result of the research shows that in the making of deed of take overagreement, in essence Notary has responsibility both morally and law.